PERSEPSI MASYAKARAT DKI JAKARTA TERHADAP FIGUR DAN KOMUNIKASI POLITIK BASUKI TJAHAJA PURNAMA (AHOK) - DANNY PRASETYO, DANNY PRASETYO (Politika: Jurnal Ilmu Politik, 2014)
A leader seeems like a captain on a ship who will lead and direct the ship towards the destination. It is not an easy matter for Basuki Tjahaja Purnama or Ahok who comes from minor ethnic to become a leader in DKI Jakarta where there once a massive race riot happened. The matter that later comes into view is how perception of DKI Jakarta citizens toward the figure of Ahok as a leader and the political communication he does. This research seeks to analyze the perception of DKI Jakarta citizens towards both the figure of Ahok as a leader and his political comunication, where in which Ahok is one of the leaders who engages the internet, in this case is social media, as a means of communication to the citizens leads. Descriptive method is applied in this research. That is a method which analyze the situation and condition of which then the result is elaborated in the research report. In this problem we analyzed, the descriptive method we used is a survey method. The research showed that in choosing a leader, people in Jakarta didn't concern about the race, religion, or tribe, but it's more to the boldness in executing the policy and the obedience to the norm and regulation. People concerned Ahok covers all those criteria and moreover he applies a new way of having a politic communication with the citizen through the internet and cell-phone. Through people think that Ahok is such a bold leader in making some innovation in politic communication, he still needs to improve the way he talks of which is so frank, and highly toned and even concerned rude. Because as a leader, Ahok is responsible to serve people in Jakarta and making them live comfortably. Keywords : political communication, figure leadership, perception